2022
DOI: 10.3390/ijms231911623
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Hepatocellular Carcinoma-Specific Immune Responses Following Hepatitis C Virus Elimination by Direct-Acting Antivirals

Abstract: Direct-acting antivirals (DAAs) have recently revolutionized the eradication of chronic hepatitis C virus (HCV) infection. However, the effects of DAAs on the development of hepatocellular carcinoma (HCC) remain unknown. Therefore, the present study aimed to investigate immune responses to HCC influenced by DAAs in HCV-infected patients and elucidate the underlying mechanisms. We compared immune responses to 19 different HCC-related tumor-associated antigen (TAA)-derived peptides and host immune cell profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…There was little correlation between TBX21 and IFN signaling-related genes in this study. Our findings showed that TBX21 was important for PD-1 related signaling involved in HCV F protein-mediated immune responses [ 29 ]. The results also showed that TBX21 was involved with PD-1, including in immune checkpoint signaling, but did not lead directly to IFN-related responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was little correlation between TBX21 and IFN signaling-related genes in this study. Our findings showed that TBX21 was important for PD-1 related signaling involved in HCV F protein-mediated immune responses [ 29 ]. The results also showed that TBX21 was involved with PD-1, including in immune checkpoint signaling, but did not lead directly to IFN-related responses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TBX21 is closely associated with SVR or non-SVR patterns induced by any antiviral drugs including DAAs or IFN. We analyzed this factor in detail with respect to the immune response that leads to hepatocarcinogenesis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are not specific for HCV Ag and are important for microbial defense and cancer immune surveillance. A previous study of HCV-infected patients with HCC found that HCV cure decreased PD-1 expression on T cells and enhanced responses to tumor-derived peptides in some cases 17 . B cell abnormalities are common during chronic HCV infection 18,19 and do not completely remit in many patients cured of HCV 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study of HCV-infected patients with HCC found that HCV cure decreased PD-1 expression on T cells and enhanced responses to tumor-derived peptides in some cases. [17] B cell abnormalities are common during chronic HCV infection [18,19] and do not completely remit in many patients cured of HCV. [20,21] In addition, the mucosal-associated invariant T cells are not restored [22] and the repertoire diversity of natural killer cells remains altered, [23] although these cells become more functional and responsive to stimulation.…”
Section: Introductionmentioning
confidence: 99%